물속의 방사성핵종(세슘) 제거율 연구 - 정관조(Gwan Jo Jeong); 손보영(Bo Young Son); 안치화(Chi Hwa Ahn); 이수원(Su Won Lee); 안재찬(Jae Chan Ahn); 김복순(Bog Soon Kim); 정득모(Deuk Mo Chung) (Daehan hwan'gyeong gonghag hoeji, 2016)
This study investigated the removal of a radioactive cesium ($Cs^+$) in the water at the water treatment processes. Since cesium is mostly present as the $Cs^+$ ion state in water, it is not removed by sand filtration, and coagulation with polyaluminum chloride (PACl), powdered activated carbon (PAC) and mixture of PACl and PAC. However, it is known that the removal rate of cesium increases as the turbidity increases in raw water. As the turbidity was adjusted by 74 NTU and 103 NTU using the surrounding solids near G-water intake and yellow soils, removal rate of cesium was about 56% and 51%, respectively. In case of a GAC filtration with supernatants after jar-mixing/setting was conducted, 80% of cesium is approximately eliminated. The experimental results show that it is efficient to get rid of cesium when the turbidity of the raw water is more than 80 NTU. In case of a GAC filtration, about 60% of cesium is removed and it is considered by the effect of adsorption. Cesium is not eliminated by microfiltration membrane while about 75% of cesium is removed by reverse osmosis. 본 연구에서는 물속에 존재하는 방사성 세슘($Cs^+$)의 정수처리 제거방법을 고찰하였다. 세슘은 물속에서 대부분 이온상태인 $Cs^+$로 존재하여 모래여과, 정수약품(PACl), 분말활성탄(PAC) 및 정수약품(PACl + PAC) 혼합주입에 의해 제거되지 않았으나 탁도가 증가함에 따라 세슘 제거율이 증가하는 것으로 나타났다. G-취수장 주변 고형물과 황토를 이용하여 탁도를 각각 74 NTU와 103 NTU로 조정했을 때 세슘의 제거율은 각각 약 56%, 51%이었으며 상징수를 GAC로 여과한 경우, 세슘의 약 80%가 제거되었다. 따라서 효과적인 세슘 제거를 위해서는 황토 등을 이용하여 원수 탁도를 80 NTU 이상 조정해야 하는 것으로 나타났다. GAC에 의한 세슘 제거의 경우, 약 60%가 제거됨을 알 수 있었으며 이것은 접촉에 따른 흡착에 의해 제거된 것으로 판단된다. 막에 의한 세슘 제거에 있어서 정밀여과막으로는 제거되지 않았으나 역삼투막에서는 75%가 제거되었다.